Synthesis, antioxidant, antimicrobial activities and molecular modeling analysis of some 5-Nitro-N-phenyl-3-(phenylamino)-1H-indazole-1-carboxamide derivatives: Docking, SAR, toxicity and molecular dynamics analysis - Mithlesh Yadav; Suraj N. Mali; Bharti Sharma; Haya Yasin; Rohit Pal; Gurubasavaraja Swamy Purawarga Matada; Archana Kapoor (Chemical Physics Impact)
This study reports the synthesis and characterization of a novel series of 5-nitro-N-phenyl-3-(phenylamino)-1H-indazole-1-carboxamide derivatives (5a-5v) obtained through the reaction of 3-chloro-5-nitro-N-phenyl-1H-indazole-1-carboxamide (4) with diverse aniline derivatives in isopropanol. The compounds underwent thorough biological evaluation encompassing antibacterial, antifungal, and in addition to antioxidant potential assessed through DPPH (IC50 = 0.105-0.513 μmol/mL) and ABTS assays (IC50 = 0.124-0.538 μmol/mL). Remarkably, compound 5b displayed exceptional antibacterial efficacy, while compounds 5k, 5p, and 5q exhibited noteworthy antifungal potential. Compound 5k showed the most significant antioxidant activity. Molecular docking studies unveiled robust binding interactions with target enzymes (PDB ID: 3SRG), and molecular dynamics simulations indicated the stability of the most active compound at the binding site. Additionally, favourable drug-likeness and ADMET properties underscore the promising therapeutic potential of these derivatives, urging further investigations for potential clinical applications. The multifaceted activities, including antibacterial, antifungal, and antioxidant properties, make these derivatives compelling candidates for in-depth exploration in the pursuit of novel therapeutic agents.